O regime jurídico das nulidades processuais e seus respectivos meios de impugnação - Garcia, Juliett Leal Gonsales (2013)
This dissertation aims to discuss the legal treatment given by the Code of Civil Procedure to Nullities arriving from the non-compliance with formal procedural aspects and accurate methodology to challenge the mentioned formalities according to the case status. In the current analysis takes into consideration the applicability of estoppel, which operates according to the severity of the formal defect incurred and, consequently their ability to produce legal effects, notably since the form cannot overlap the essence of procedural acts except in cases when the defect occurs in sufficient grounds to affect the merits of the case, namely in the case of absence or legal nullity absolute